2013
DOI: 10.1200/jco.2013.31.15_suppl.9602
|View full text |Cite
|
Sign up to set email alerts
|

The unmet needs of cancer survivors and their preferences for discussing them with oncologists and general practitioners (GPs).

Abstract: 9602 Background: Cancer survivors experience a range of post-treatment issues which are not well met by current services. This study explores the unmet needs of adult cancer survivors and their levels of comfort in addressing issues with oncologists and GPs. Methods: A cross-sectional survey was mailed to adult cancer survivors 4 years from diagnosis from 6 oncology units. Self-report data were obtained ranking physical, psychological and practical areas of importance to survivors; unmet needs in these areas;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the first study, 20 a survey of survivors of various cancer types, participants indicated they preferred to discuss diet with their General Practitioner (GP) rather than their oncologist. However, 51% of participants reported they did not feel comfortable discussing diet with either their GP or oncologist 20 . The survey did not explore the reasons for these preferences, or provide an option for participants to indicate a preference for receiving dietary information from a nutrition professional.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first study, 20 a survey of survivors of various cancer types, participants indicated they preferred to discuss diet with their General Practitioner (GP) rather than their oncologist. However, 51% of participants reported they did not feel comfortable discussing diet with either their GP or oncologist 20 . The survey did not explore the reasons for these preferences, or provide an option for participants to indicate a preference for receiving dietary information from a nutrition professional.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer survivors’ experiences regarding the provision of dietary information post‐treatment were reported in nine of the 12 included studies 20,22,24,25,27–31 . In eight of these studies, cancer survivors reported that treatment providers often did not provide dietary information post‐treatment or explain the role of diet in recovery from cancer treatment 20,22,25,27–31 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations